Déterminants biologiques et maternels des problèmes de comportement chez l'enfant inuit d'âge scolaire - Bégin, Gabrielle (Université Laval, 2016)
This research project aims to document the association between multiple biological and psychosocial determinants and the emergence of behavioural problems among schoolaged Inuit children. The objectives are firstly to document the presence of these risk factors through descriptive statistics and secondly, test the association with the development of externalizing and internalizing behaviour problems in a sample of eleven-year-old children. 294 Inuit aged between 8 and 14 years living in Nunavik were invited to participate in this longitudinal study. The Teacher's Report Form of the CBCL was faxed to the child's school for his teacher to complete. Pearson correlations and multiple regressions were performed on variables significantly associated with behaviour problems. The results of the correlations show that biological determinants are not associated with the occurrence of internalizing behaviour problems (IBP), and that gender and tobacco consumption during pregnancy are correlated with the appearance of externalized behaviour problems (EBP). In addition, prenatal drug use and breastfeeding have marginally significant correlations with EBP. Regression analyzes show the effects of child gender, prenatal exposure to tobacco, the Raven score and food insecurity are significantly associated with the occurrence of EBP, while the score at Raven and language during the interview, when combined, account for the emergence of IBP. In light of these results, questions remain and are discussed in conclusion. Le présent projet de recherche propose de documenter l’association entre certains déterminants biologiques et psychosociaux et l’apparition de difficultés de comportement chez des enfants inuits d’âge scolaire. Les objectifs sont d’une part de documenter la présence de ces facteurs de risque au moyen de statistiques descriptives et d’autre part, de vérifier l’association avec l’apparition de problèmes de comportements externalisés et internalisés chez les enfants âgés de 11 ans. 294 enfants inuits âgés entre 8 et 14 ...